Moderators of Cognitive Outcomes from an Exercise Program in People with Mild to Moderate Dementia. Issue 9 (22nd May 2020) - Smith, Toby O.; Mistry, Dipesh; Lee, Hopin; Dosanji, Sukhdeep; Finnegan, Susanne; Fordham, Bethany; Nichols, Vivien P.; Sheehan, Bart; Lamb, Sarah E.
Abstract : BACKGROUND/OBJECTIVES: Our aim was to estimate whether baseline participant variables were able to moderate the effect of an exercise intervention on cognition in patients with mild to moderate dementia. DESIGN: Subgroup analysis of a multicenter pragmatic randomized controlled trial. SETTING: Community‐based gym/rehabilitation centers. PARTICIPANTS: A total of 494 community‐dwelling participants with mild to moderate dementia. INTERVENTION: Participants were randomized to a moderate‐ to high‐intensity aerobic and strength exercise program or a usual care control group. Experimental group participants attended twice weekly 60‐ to 90‐minute gym sessions for 4 months. Participants were prescribed home exercises for an additional hour per week during the supervised period and 150 minutes each week after the supervised period. MEASUREMENTS: Multilevel regression model analyses were undertaken to identify individual moderators of cognitive function measured through the Alzheimer Disease Assessment Scale‐Cognitive Subscale score at 12 months. RESULTS: When tested for a formal interaction effect, only cognitive function assessed by the baseline number cancellation test demonstrated a statistically significant interaction effect (−2.7 points; 95% confidence interval = −5.14 to −0.21). CONCLUSION: People with worse number cancellation test scores may experience greater progression of cognitive decline in response to a moderate‐ to high‐intensity exercise program. Further analyses to examine whether these findings can be replicated in planned sufficiently powered analyses are indicated.